Severe Complications after Corneal Collagen Cross-Linking (CXL) - Blaser, Frank; Zweifel, Sandrine; Wiest, Maximilian Robert Justus; Bajka, Anahita; Said, Sadiq; Barthelmes, Daniel; Muth, Daniel Rudolf (Klinische Monatsblätter für Augenheilkunde, 2023)
Purpose To present a case series of rare and severe complications after corneal collagen cross-linking (CXL) of keratoconus patients.Methods Single-center descriptive case series covering the period of 2012 to 2022 at the Department of Ophthalmology at the University Hospital, Zurich, Switzerland.Results We present four eyes of four patients that showed severe unusual complications within the first month after CXL. Three patients had been treated with the classical epithelium-off “Dresden” protocol. One patient had been treated with the accelerated epithelium-off protocol. One patient presented with extensive corneal edema due to rubbing the eye after treatment. Two patients showed a bacterial infectious keratitis: one due to Streptococcus pneumoniae and the other due to Staphylococcus hominis, Micrococcus luteus, and Streptococcus epidermidis. The latter of the two patients exhibited extensive infectious crystalline keratopathy. The fourth patient showed a severe ulcerative lesion where no infectious cause could be found. Therefore, an autoimmune keratolytic process had to be suspected. Apart from the corneal edema, which resolved ad integrum, the other complications resulted in permanent corneal scarring and thinning. One patient needed an emergency amniotic transplant.Conclusion Severe complications after CXL remain rare. Most common causes are complications that are not directly associated with the treatment as such. Those indirect complications occur after the treatment during the healing course of the epithelium. Associations with bandage contact lenses, topical steroids, atopic disease, and inappropriate patient behavior are often suspected. Correctly performed corneal scrapings with repeated microbiological analysis and a detailed patient history are essential for establishing the correct diagnosis, especially in complicated cases that do not respond to a standard therapeutic regimen. This case series supports the efforts that are currently taken to improve the CXL technique in a way that postoperative complications are further reduced. A more efficient epithelium-on technique might be a step in that direction.
Keywords: corneal collagen cross-linking (CXL); keratoconus; complications; keratitis; epithelium on off